Desain Rangkaian Gate Driver Analog untuk Dual Mosfet Drivers - Hendi Matalata; Rozlinda Dewi (Universitas Batanghari Jambi, 2021)
Switching techniques have been continued to develop, including sinusoidal PWM, space vector PWM, current tracking PWM, harmonic elimination PWM and others. Each method has advantages and disadvantages, but the most commonly used methods are sinusoidal PWM and space vector PWM. PWM that is generated using a microcontroller or analog IC component generally has a maximum voltage value of 5V. To strengthen the PWM wave, a gate-driver circuit is needed, so that the PWM control wave is able to move the IGBT / MOSFET. On this paper, the design of gate driver circuit use An analog IC, which starts from the generation of two waves, namely a sinusoidal wave and a DC source to be compared (Comparator) so that it can produce a PWM wave. Then this PWM wave is isolated using an optocoupler and MOSFET driver IC to limit interference in the switching process on high power supplies. Based on the results, it can be cancluded PWM control wave output from the gate-driver circuit is isolated from the system intended for designing a power converter and other applications.